Analysis of graduate students' access and utilization of e-learning technology in a Nigerian university (2008)
Nigeria is a third world country where access and utilization of e-learning technology arc generally low. This study investigated through empirical methods the extent to which a randomly selected sample of 406 graduate students had access to and utilized the c-learning technology. It adopted the survey research design, using a checklist type of questionnaire with a reliability co-efficient of 0.86. Percentages, Pearson Product Moment Correlation and multiple regression were used for data analysis at 0.05 level of significance. The findings revealed that graduate students had adequate access to available c- learning technologies, but their literacy and utilization rates were very low. The incorporation of application of c-learning technologies to the curricula was recommended, with the view that this will compel learners to improve both their literacy and utilization levels.